New species of Asphalidesmus Silvestri, 1910 from Australia (Diplopoda, Polydesmida, Dalodesmidea) - Robert Mesibov (ZooKeys, 2011)
Asphalidesmus allynensis sp. n. and A. dorrigensis sp. n. are described from New South Wales, A. otwayensis sp. n. from Victoria, and A. bellendenkerensis sp. n., A. carbinensis sp. n., A. magnus sp. n. and A. minor sp. n. from Queensland. The previously endemic Tasmanian genus Asphalidesmus Silvestri, 1910 is now known from 16°S to 43°S in eastern Australia, a north-south range of ca 3000 km. Asphalidesmus spp. throughout this range are very similar in overall appearance. Three of the new species are able to coil in a tight spiral.